2018
DOI: 10.3390/s18020503
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Driver Distraction Identification On-The-Road via Continuous Decomposition of Galvanic Skin Responses

Abstract: One of the main reasons for fatal accidents on the road is distracted driving. The continuous attention of an individual driver is a necessity for the task of driving. While driving, certain levels of distraction can cause drivers to lose their attention, which might lead to an accident. Thus, the number of accidents can be reduced by early detection of distraction. Many studies have been conducted to automatically detect driver distraction. Although camera-based techniques have been successfully employed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Emotional changes will lead to changes in sweat gland secretion, which in turn will lead to changes in skin conductivity resulting in changes in the skin electrical index. Electrodermal activity is strongly correlated with mood, attention, and arousal, and researchers have widely used the electrodermal index to describe driver stress levels [46], [47]. Studies have shown that the skin conductance response should be chosen as a parameter to study when the level of psychological change is low, and the present study is a low-strain research on the change of driver stress level under normal driving conditions [48].…”
Section: B: Electrodermal Activitymentioning
confidence: 93%
“…Emotional changes will lead to changes in sweat gland secretion, which in turn will lead to changes in skin conductivity resulting in changes in the skin electrical index. Electrodermal activity is strongly correlated with mood, attention, and arousal, and researchers have widely used the electrodermal index to describe driver stress levels [46], [47]. Studies have shown that the skin conductance response should be chosen as a parameter to study when the level of psychological change is low, and the present study is a low-strain research on the change of driver stress level under normal driving conditions [48].…”
Section: B: Electrodermal Activitymentioning
confidence: 93%
“…There are other measures such as sensitivity, precision, and training time that have been considered to compare the algorithms in some studies [25] [27] [28]. However, just accuracy was considered in this study as it was the primary measure in most papers we reviewed [68]. The accuracy metric was chosen because of the balanced nature of the classes coupled with the high numbers for true positives and true negatives in confusion matrices.…”
Section: Feature Selection and Classifier Constructionmentioning
confidence: 99%
“…Significant advances for the prediction of driver drowsiness and workload have been made in association with the use of more sophisticated features of physiological signals, as well as from the application of increasingly sophisticated machine learning models, although extrapolation of such to the context of commercial pilots has not yet been attempted. Some approaches have been based on EDA signal decomposition into tonic and phasic components [66], extraction of features in time, frequency, and time-frequency (wavelet based) domains [67], or the use of signal-entropy related features [68].…”
Section: Human Factors and Their Limitsmentioning
confidence: 99%